Deservingness and temporal borders: the reproduction of global mobility hierarchies in Swedish family reunification - Gustafsson, Hilda; Engblom, Rikard (Frontiers in Sociology, 2024)
European immigration policy is increasingly selective and stratified, favoring immigrants considered productive in the eyes of society. Using the case of Swedish family reunification, this article investigates how ideas of deservingness underlie this selection process and how it intersects with temporal bordering, impacting hierarchies of transnational mobility. Through qualitative interviews with individuals across a spectrum of legal statuses, the study finds that the increased connection between immigration policy and the housing and labor markets, combined with restrictions concerning visas, age, and legal status, induce and reproduce inequalities in waiting times and access to reunification. Within these restrictions, however, families find ways to circumvent the wait and get family time. The study contributes to the temporal turn in migration studies by exploring reunification among families with diverse backgrounds, complementing previous literature’s focus on the experiences of forced migrants. By considering how deservingness and temporal bordering shape mobility, the article offers both conceptual and empirical contributions to mobility and migration studies. Ultimately, the study brings forward a nuanced analysis of the consequences of restrictive shifts in Swedish immigration policy, contributing to the broader understanding of the current, transnational, mobility regimes.